Pelestarian Seni Bendrong Lesung dari Cilegon - Rahmandito Dwiatno; Didit Widiatmoko Soewardikoen (Syntax Literate, 2022)
Bendrong Lesung is a traditional art originating from Cilegon, a performing art using the sound of a mortar and pestle as the main instrument. This art is fading along with the development of modern technology, which has provided more interesting entertainment so that there is no interest from the younger generation to continue this art. There needs to be conservation efforts so that it can be passed on to the next generation. This study uses a qualitative approach by conducting participatory observations of the object of research, interviews and literature studies. The results will be used for the development of interactive game applications, to be used by the younger generation so that the preservation of this art can be carried out.